Pengaruh Green Advertising Versi #BBOB Dan Green Brand Image Terhadap User Attitudes - Shakila Mutiara Asthi Sepnita Asyril; Sarah Samaria (STIKes Ibnu Sina Ajibarang, 2024)
The rise of eco-friendly products, makes advertising connected with protection efforts. One of the pioneer companies in green marketing to socialize zero waste is The Body Shop Indonesia. The Body Shop often emphasizes the attitudes of social values ​​and concern for the environment and then issues a campaign and advertisement which is often called Bring Back Our Bottles (BBOB). The purpose of this study was to determine the effect of green advertising version of #BBOB and green brand image on user attitude at The Body Shop Indonesia. Using a quantitative method by distributing questionnaires to 100 respondents with non-probability sampling. This study uses the S-O-R (Stimulus -Organism - Response) theory which is in accordance with the research phenomenon. The results show that green advertising and green brand image affect user attitudes in the bring back our bottles ad from The Body Shop Indonesia. Based on the results of research that has been tested using SPSS software through various tests and using the S-O-R theory it can be concluded that there is an influence of green advertising and green brand image which can be the latest innovation in developing marketing ideas so that they can influence user attitudes at The Body Shop Indonesia in a bring back our bottles advertisement.